IS DISTANCE e-LEARNING OPTION ACCEPTABLE BY NIGERIANS AMIDST COVID-19 PANDEMIC? - Hassan, Zubaida; Sa'id, Aisha Shitu; Mohammed, Hassan Adamu (African Journal of Education and Practice, 2021)
Purpose: In Nigeria, the current COVID-19 Pandemic stands-still virtually all formal learning activities, especially in Government owned institutions. Therefore, the aim of this study was to assess the perception and readiness of Nigerians on adapting Distance e-Learning option during and even after the COVID-19 Pandemic. Methodology: The study applied a quantitative cross-sectional design approach. A closed-ended e-questionnaire was designed using google form and distributed in a snowball fashion-wise via online platforms. Three categories of the audience were targeted: teachers, students and parents. Descriptive statistics were used to analyze responses. ANOVA was used to analyze the collective decision across the three categories. Findings: The findings revealed that there is no difference amongst the three groups in their final decisions on willingness to adapt (F (0.187), p-value 0.83), and kick-start distance learning (F (0.469), p-value 0.63). Poor internet infrastructure and unstable electricity supply were some of the challenges identified. Unique contribution to Theory, Practice, and Policy: The study highlights the willingness of Nigerians in adapting distance e-learning approach as a viable alternative to traditional face-face learning amidst COVID-19 Pandemic and beyond. Administrative involvements are crucial to actualizing this educational dream of Nigerians.